Immune checkpoint molecules soluble program death ligand 1 and galectin‐9 are increased in pregnancy. (4th December 2017) - Enninga, Elizabeth Ann L.; Harrington, Susan M.; Creedon, Douglas J.; Ruano, Rodrigo; Markovic, Svetomir N.; Dong, Haidong; Dronca, Roxana S.
Abstract : Problem: Pregnancy requires balance between tolerance to the haploidentical fetus and the mother's ability to mount immune responses. There are parallels to this phenomenon that occur in metastatic cancer. We assessed soluble program death ligand‐1 soluble PD‐L1 (sPD‐L1) and galectin‐9 in the blood of pregnant women during gestation as these molecules are highly involved in immune suppression during cancer. Method of study: Maternal blood was collected from 30 primigravida women at monthly intervals during pregnancy, delivery and 6‐week post‐partum. Blood was analyzed for sPD‐L1 and galectin‐9 concentrations by ELISA. Term placentas were collected in formalin and IHC was completed for PD‐L1 and galectin‐9 expression. Results: Maternal blood levels of sPD‐L1 (0.438 ng/mL) and galectin‐9 (1976 pg/mL) were elevated early in normal pregnancies compared to non‐pregnant controls (0.242 ng/mL and 773 pg/mL, respectively). sPD‐L1 increased throughout gestation, whereas galectin‐9 remained elevated until parturition; both proteins returned to control levels post‐partum. Women carrying male fetuses had significantly higher galectin‐9 levels, but not sPD‐L1, than those carrying females (2263 pg/mL vs 1874 pg/mL; P  = .0005). Trophoblast cells of the term placenta coexpress galectin‐9 and PD‐L1. Conclusion: Immune‐regulatory molecules galectin‐9 and sPD‐L1 increased during pregnancy and may play a role in immune tolerance that is critical for the fetus. Abstract : Normal human pregnancy is associated with increased levels of immunosuppressive soluble program death ligand‐1 (sPD‐L1) and galectin‐9.